Coexistence of systemic lupus erythematosus after TNF inhibitor therapy in patient with ankylosing spondylitis - Tongthong, Wanwaleeya; Marungruang, Jenpop; Angthararak, Sungchai (Thai Journal of Rheumatology, 2024)
A 33-year-old single Thai male was diagnosed with ankylosing spondylitis that not responded to treatment with conventional disease-modifying antirheumatic drugs (csDMARDs) then he received tumor necrosis factor (TNF) inhibitor and developed anemia and thrombocytopenia and positive test for antinuclear antibody (ANA) positive 1:320 homogeneous pattern, it is considered secondary to systemic lupus erythematosus (SLE) induced by the use of TNF inhibitors.